Molecular characterization of yohimbine hydrochloride using vibrational spectroscopy and quantum chemical calculations - Joshi, Bhawani Datt; Tandon, Poonam; Jain, Sudha (BIBECHANA, 2012)
In this work, we have performed the extraction of yohimbine hydrochloride (C21H27ClN2O3) (YHCl). The optimized geometry, total energy, potential energy surface and vibrational wavenumbers of YHCl have been determined by using ab initio Hartree–Fock (HF) and density functional theory (DFT/B3LYP) method with 6-311++G(d,p) basis set. The calculated wavenumbers are scaled by a proper scaling factor. A selected number of vibrational assignments are provided for the observed Raman and IR spectra. Keywords: YHCl; vibrational spectroscopy; ESP; ab initio and DFT calculations DOI: http://dx.doi.org/10.3126/bibechana.v8i0.4923 BIBECHANA 8 (2012) 73-80